Sistem Monitoring Gas Oksigen dan Karbondioksida pada Ruang Penyimpanan Sistem Udara Terkontrol - Argo, Bambang Dwi; Lastriyanto, Anang; Astuti, Nuraini Puji (Rekayasa Mesin, 2010)
One of way in pickling process of main food material of vegetable and fruits is storage. In principle metabolism storage, like respiration, transpiration, infection plant diseases and lengthen more durable. Purpose of storage of fruit and vegetable to lengthen product usefulness, controls request of market and increases advantage. At research before all, the system controlled atmosphere storage still be done in manual either from within observation of composition and operation of gas in it. Therefore, need to be done modification of equipment with addition of monitoring system and gas control automatically, so that change of gas volumein storage space of CAS can be detected. Equipment applied in this research is microcontroller AT89S51 and its arrangement system by using computer. With existence of communications between microcontroller system with personal computer through IC RS 232. At this researc happened change of oxygen gas concentration from 21% to 2% and increase of percentage of carbondioxide from 0.03% to 2.5% for temperature 26oC. this matter is according to boundariset wanted for condition of apple atmosphere Rome Beauty.Keywords : Oxygen, carbondioxide, CAS, MKAT89S51, Personal Computer (PC)